1999
DOI: 10.1093/hmg/8.11.1967
|View full text |Cite
|
Sign up to set email alerts
|

A novel deficiency of mitochondrial ATPase of nuclear origin

Abstract: We report a new type of fatal mitochondrial disorder caused by selective deficiency of mitochondrial ATP synthase (ATPase). A hypotrophic newborn from a consanguineous marriage presented severe lactic acidosis, cardiomegaly and hepatomegaly and died from heart failure after 2 days. The activity of oligomycin-sensitive ATPase was only 31-34% of the control, both in muscle and heart, but the activities of cytochrome c oxidase, citrate synthase and pyruvate dehydrogenase were normal. Electrophoretic and western b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(26 citation statements)
references
References 45 publications
2
24
0
Order By: Relevance
“…1). Transmitochondrial cybrid cells made of patient's fibroblasts fully complemented the ATPase defect and confirmed the nuclear origin of impaired biogenesis of the enzyme complex [27]. Later on, two other similar cases of selective ATPase deficiency were found in the Czech Republic [22] and one in Austria [28].…”
Section: Atpase Defects Of Nuclear Originmentioning
confidence: 61%
See 2 more Smart Citations
“…1). Transmitochondrial cybrid cells made of patient's fibroblasts fully complemented the ATPase defect and confirmed the nuclear origin of impaired biogenesis of the enzyme complex [27]. Later on, two other similar cases of selective ATPase deficiency were found in the Czech Republic [22] and one in Austria [28].…”
Section: Atpase Defects Of Nuclear Originmentioning
confidence: 61%
“…An extremely low ATPase activity and low, tightly coupled, respiration rates were observed in muscle mitochondria, but no mutation was found in mtDNA genes encoding ATPase subunits. The nuclear origin of ATP synthase deficiency was demonstrated for the first time in 1999 [27] in a new type of fatal mitochondrial disorder. A child with severe lactic acidosis, cardiomyopathy and hepatomegaly died 2 days LA-lactic acidosis, CM-cardiomyopathy.…”
Section: Atpase Defects Of Nuclear Originmentioning
confidence: 99%
See 1 more Smart Citation
“…Although complex V deficiency caused by nuclear gene mutations has already been shown in 1999 (Houstek et al, 1999), it took until 2004 when such a mutation was found in the ATP12 gene (De Meirleir et al, 2004). ATP11, ATP12 and FMC1 are the presently known genes that encode for proteins involved in the assembly of the F 1 part in yeast, of which only ATP11 and ATP12 are found in human.…”
Section: Complex Vmentioning
confidence: 99%
“…CI in RCE disorders comprises ECG abnormalities [4, 5, 6], myocardial thickening (fig. 2), dilatation [6]and heart failure [56, 57]. A dominant feature of CI in RCE disorders seems to be ILVAT [58, 59].…”
Section: Myopathies With Cardiac Involvementmentioning
confidence: 99%